Relevansi Filsafat Ilmu Terhadap Pengembangan Kurikulum: Kajian Literatur Review: Penelitian - Widuri, Ratih; Susanti, Rahmi; Yosef, Yosef; Chotimah, Umi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the relevance of the philosophy of science in curriculum development through a literature review approach. Philosophy of science, serving as an epistemological, ontological, and axiological foundation, plays a strategic role in determining the direction, substance, and methodology of curricula that respond to scientific and educational advancements. This review synthesizes recent literature that discusses the connection between the philosophy of science and curriculum design across various educational levels. The results indicate that the ontological dimension supports the formulation of curriculum content, the epistemological dimension strengthens the selection of instructional approaches, and the axiological dimension ensures that curriculum development aligns with values, ethics, and learner benefit. The findings also show that integrating the philosophy of science supports the creation of curricula that are more adaptive, critical, and contextually relevant to global changes. Additionally, this review identifies a research gap regarding the limited explicit integration of the philosophy of science in national curriculum frameworks. Overall, the study underscores the urgency of reinforcing philosophical perspectives in curriculum development to enhance the comprehensive quality of education.